Fourier transforms in radar and signal processing - Brandwood, David (Artech House radar library., 2003)
"Fourier transforms are used widely, and are of particular value in the analysis of functions and combinations of functions found in radar and signal processing. Still, many problems that could have been tackled by using Fourier transforms may have gone unsolved because they require integration that is difficult and tedious. Now practitioners can solve many of these problems with the integration-free approach to carrying out Fourier transforms (and Fourier series) presented in this unique book." "By building upon Woodward's well-known "rules and pairs" method and related concepts and procedures, the book establishes a unified system that makes implicit the integration required for performing Fourier transforms on a wide variety of functions. It details how complex functions can be broken down to their constituent parts for analysis. The approach presented in this book allows professionals to concentrate on functional relationships instead of getting bogged down in the details of integration. Moreover, the book includes specific examples in the areas of digital signal processing, radar, and antenna operation."--Jacket